English adjective phrase variations of bloggers from two Myanmar ethnic groups - Phyu, Hnin Pwint; Mohammad Lotfie, Maskanah (Faculty of Languages and Communication, Universiti Sultan Zainal Abidin, 2015)
Blogs have become an undeniably important source of information on sociopolitical occurrences in Myanmar, especially concerning the conditions of its minorities including the Rohingya. However, Myanmar bloggers are non-native speakers of English and their mother tongues belong to different language families of unique historical backgrounds. These differences may have significant effects on the English language production of the bloggers. This study specifically explores variations of adjective phrases used by Burmese and Rohingya bloggers. Adjectival modifiers are very important in the content of blogs as they are linguistically instrumental in the narrations, descriptions and analyses of incidents and issues. Adjective phrases collated from forty blog articles have been thoroughly analysed. The findings of this exploratory study suggest essential theoretical and pedagogical implications. Among others, it can be concluded that Rohingya bloggers’ use of adjective phrases are more frequent than Burmese bloggers’. Specifically, they have been found to considerably use more adjective phrases with complements than their Burmese counterparts.